Portfolio 2001 informed investment in the new millenium - Katz, John (Random House Business Books, 1996)
The three point strategy for picking the best investments worldwide is as follows: make informed buying decisions and safeguard investments by monitoring; focus on long-term value with investments that grow earnings year after year: profit from the Internet and use vital information in real time at low cost. There are recognisable sectors where global companies are on course to grow profits well into the twenty-first century. Companies in life sciences, technology, communications, entertainment and media are seen as innovators and their use of new science and technology will have a marked influence on their future profits. The great consumer brands such as Coca Cola, Nestle and Carlsberg are also worth watching closely, as are companies set to win exceptional benefits from the Millennium celebrations-De Beers, British Airways, champagne producers. Access to research and information will make or break an investment strategy. John Katz presents the kind of information professionals rely on in a jargon-free style for the private investor. His information includes comprehensive analysis of facts and figures, earnings forecasts and share price targets to the year 2001. A guide to using the Internet to update information, research new prospects and monitor holdings.